Perceptions of Chinese higher-vocational nursing program directors on digital transformation: A qualitative study - Kaixuan Duan; Fangqun Mao; Ruiming Li; Xiaofeng Jin; Hao Huang; Meng Wen (PLoS ONE, 2026)
Background Currently, most research on digital transformation in higher vocational education conducts macro-level analyses, and few comprehensive studies specifically address higher vocational nursing education. Moreover, research is notably lacking on the perceptions of Chinese higher vocational nursing program directors, and the prevalent utilization of digital tools within this field remains underexplored. Objective To understand the perceptions and experiences of higher vocational nursing program directors regarding the use of digital transformation tools in nursing education. Methods This qualitative study employed semistructured interviews conducted with 14 program directors from higher vocational nursing programs. The interview data were transcribed, and Colaizzi’s seven-step method was used for a subject analysis. Results The study employed Colaizzi’s seven-step framework for inductive thematic analysis, with coding conducted collaboratively until data saturation was achieved. Analysis revealed four principal themes: (1) Recognition of digital education by program directors, where enthusiasm for enhanced engagement and transcended geographical barriers coexisted with unspoken doubts about resource quality and the authenticity of student participation; (2) Perceived status and impact of digital infrastructure, characterized by significant hardware investments yet inconsistent resource quality and utilization—revealing a fundamental gap between technological abundance and meaningful pedagogical integration; (3) Systemic Tensions and Barriers, exposing profound contradictions between policy aspirations and classroom realities, generational divides in educational philosophies among teachers, and persistent disconnects between technology’s promise and its operational friction, all of which contributed to increased workloads and a pervasive sense of professional role dissonance; (4) Strategic Approaches to Digital Transformation, centered on increasing investment, fostering educator development, promoting resource sharing, and strengthening industry-education integration. Conclusion Higher vocational nursing program directors recognize the value of digital education, yet its adoption is constrained by challenges in platform usability and a lack of supportive institutional incentives. Effective transformation requires systemic strategies that enhance the digital ecosystem's ease of use, align professional rewards with innovation, and promote cross-sector collaboration to develop pedagogically sound resources.